Innovation and technological endeavor in the European Union (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The success of the transition to the knowledge-based economy, as strategic goal set in Lisbon by the European Council, requires the study of the role of the process ofinnovation in the EU during this period. We first describe theoretical issues regarding effects of innovation and technological change on economic growth. Secondly, wediscuss the different national patterns and analyse the regional disparities research and development activities between the UE-25. Finally, we put forward some recommendations for further policy reforms.
Keywords: innovation; regions; European Union; R&D